Implementation and evaluation of a weight-reduction programme for diabetic patients at a primary health care facility in the Western Cape: a pilot study - Adil Razak; Abdul Aziez Isaacs (South African Family Practice)
Background: Diabetes is a common non-communicable disease and complications are resulting in increased disability, reduced life expectancy and enormous health costs for virtually every society. Medical Nutrition Therapy is important for the prevention, treatment, and self-management of diabetes, and the prevention or delay in onset of diabetes-related complications. The current nutritional guidelines for diabetes state that carbohydrates should comprise 45–60% of the total nutritional intake and that lowcarbohydrate or high-protein diets offer no long-term success over healthy eating plans. Recent studies suggest that there may be merit in using low-carbohydrate diets in diabetic patients for weight reduction and improved cardiovascular markers. This study aimed to implement and evaluate a pilot programme for weight loss in diabetes mellitus type 2 patients by comparing a low-carbohydrate diet with the conventional low-fat diet.